Public sector efficiency and small island developing states - Simon Feeny; Mark Rogers (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper examines the efficiency of public sector expenditures at achieving social sector outcomes in small island developing states (SIDS). Public sector efficiency is estimated using a stochastic production function (SPF) approach and panel data since 1990. A second stage of the analysis examines the determinants of efficiency. Results indicate that the efficiency of public sectors at improving life expectancy has deteriorated during the 1990s but efficiency at improving school enrolments has increased. Higher levels of governance are associated with higher public sector efficiency. There is also evidence to suggest that efficiency is lower in SIDS, as well as in Sub-Saharan Africa.
Keywords: H11; H51; H52; 330; public sector expenditures; efficiency; life expectancy; school enrolments; Öffentliche Sozialausgaben; Wirkungsanalyse; Sterblichkeit; Bildungsverhalten; Kleinstaat; Insel; Entwicklungsländer